Influence of Mn content on microhardness in Zn-Mn/CNF cubical cast alloys: a 3D topographical study - Chan, Kar Fei; Yaakob, Yazid; Tanemura, Masaki; Mohd Yusop, Mohd Zamri (Elsevier Ltd, 2025)
Zinc (Zn) is a unique biodegradable material that shows promise in terms of acceptable biomechanical properties, lower melting energy consumption, and improved recyclability. These characteristics provide fresh perspectives for producing medical implants in large quantities. However, coarsened microstructures are usually present in cast pure Zn, which leads to insufficient synergistic control over mechanical hardness. This work involved the fabrication of a zinc-manganese with carbon nanofiber alloy (Zn-Mn/CNF) using melt-casting under ambient conditions. The molten mixture was cast into a 10 mm × 10 mm mould for further characterization. The XRD investigation indicated the presence of Zn and Mn0.02Zn1.98 crystals in the fabricated alloy, which enhanced the microhardness. The microstructure of the as-cast alloy consisted of columnar grains, with no equiaxed grains observed. The combining effect of CNF and Mn reduces the size of columnar grains from 1.40 to 0.44 mm² via continuous dynamic recrystallization (CDRX). The enhancement of microhardness by approximately 17 % was attributed to the solid solution strengthening effect. The microhardness across the columnar grain was observed, and it resulted from the large gradient structure and the Hall-Petch softening effect. This research elucidated the crystallographic, microstructural, and microhardness characteristics of small-volume casting Zn alloy, offering theoretical foundations for its application in medical implants.